KONSELING KELUARGA DALAM MENGEMBANGKAN NILAI-NILAI KEARIFAN LOKAL PADA POLA PIKIR ANAK - Aisyah Khumairo (Jurusan PGMI FTIK IAIN Metro Lampung, 2017)
Family as the first and the nearest environment has primary responsibility in the value of education to children. Parenting activities conducted by parents in the family is one form of educational process of cultural values ​​as a whole. The importance of multicultural education given to children early with the hope that the child is able to understand that in their environment and also in other environments are cultural diversity. The present article intends to provide an overview and ideas on family counseling in developing local knowledge in the mindset of children by conducting a literature review that looked at family counseling can become an alternative program to realize the love child of the local culture. There are two approaches to do in this case: 1). Individual approach or also called individual counseling which attempts to explore emotions, experiences and thoughts klien. 2). Family Conseling, discussion in families led by a family counselor.